2021
DOI: 10.3390/met11060931
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Flake Powder Metallurgy Research

Abstract: This paper reviewed several recent progresses of the new powder metallurgy technology known as flake powder metallurgy (FPM) including different processing routes, conventional FPM (C-FPM), slurry blending (SB), shift-speed ball milling (SSBM), and high-shear pre-dispersion and SSBM (HSPD/SSBM). The name of FPM was derived from the use of flake metal powders obtained by low-speed ball milling (LSBM) from spherical powder. In this case, the uniformity of reinforcement distribution leads to increased strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…In addition, since MMR process typically provide an elongated UFG microstructure in longitudinal direction [5,6,[13][14][15], therefore, the geometry effect should to be take into account in the calculation. To this end, influences of geometry of deformation on the density of HAGBs is studied by Razavi et al [68] and a technique is proposed to calculate this effect.…”
Section: Deformation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, since MMR process typically provide an elongated UFG microstructure in longitudinal direction [5,6,[13][14][15], therefore, the geometry effect should to be take into account in the calculation. To this end, influences of geometry of deformation on the density of HAGBs is studied by Razavi et al [68] and a technique is proposed to calculate this effect.…”
Section: Deformation Modelmentioning
confidence: 99%
“…As an effective way of improving material properties, especially mechanical strength and ductility, severe plastic deformation techniques have been proposed [6,[9][10][11][12]. Powder metallurgy (PM) by means of low-speed ball milling (LSBM) has been reported as a beneficial approach for preparing CNT/Al with CNT dispersion with a high level of uniformity by means of changing the spherical ductile metal powders into flake-shaped building blocks (the flake PM approach) [5,6,[13][14][15]. During the cold-welding stage, the flaky powders are cold-welded into a lamellar structure, and the CNTs are introduced into the ductile powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During milling, the morphology of particles with a soft matrix changes to a plate-like morphology, and then, with increase in deformation and occurrence of work hardening and brittleness, these plate-like particles break into smaller particles [16,18,33]. However, increment of PCA amount leads to lower deformation and work hardening in particles Figure 3 illustrates the SEM images of the powders synthesized in the presence of different amounts of PCA with different magnifications.…”
Section: Effect Of Process Control Agent Amountmentioning
confidence: 99%
“…In addition, the studies reported that horizontal-type milling is advantageous to accomplish the homogeneous distribution of the powder as compared to vertical-type milling systems such as the attritor milling system in which the powder segregation occurs (dead-zone formation) due to the gravity effect [ 19 ]. The evolution of microstructure could be controlled by the milling parameters, especially the milling speed [ 20 ]. In this study, the flake-shaped Ni powders are produced through a horizontal-type high-energy ball milling process.…”
Section: Introductionmentioning
confidence: 99%